Analysis of the Implications of Organizing Sports on Economic Growth (A Literature Review) - Doni Pranata; I Putu Agus Dharma Hita; Elsa Ariestika; Witri Suwanto (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2023)
Economic development is a series of activities carried out in a systematic and structured manner in the economic sector which causes the goods and services produced in society to increase and increase for the community. In the current era, economic growth is marked as an indicator for achieving the success of the development of a region. The purpose of this study is to see how the influence and impact of the sports sector to improve economic development on a micro and macro basis. The type of research adapted is library research or more commonly known as library research, using descriptive analysis of research. The data analyzed is data that comes from previous studies to be analyzed and described so that conclusions can be drawn. The data collection method used is literature study research consisting of various sources including primary and secondary sources. The results obtained from the research are that there are implications of organizing sports on economic growth for actors and the community around the place where sports are held. society so as to create economic growth.